PENGARUH METODE PEMBELAJARAN DAN MINAT BELAJAR TERHADAP PEMAHAMAN PHYSICAL SCIENCE - Meilina, Meilina (JISPE Journal of Islamic Primary Education, 2021)
The purpose of this study was to determine the effect of learning methods and interest in teaching on the understanding of physical science in first grade elementary school children in Pasaman Regency 2020. The research method used the experimental method with a 2 x 2 factorial design. The data analysis technique used two-way ANAVA and Tukey's test with a significance level of α = 0.05. The results of this study indicate: 1) The understanding of physical science of children who are taught by the discovery learning method is higher than that of children taught by the project-based learning method (= 21,70 > 3.97), 2) There is an interaction between learning methods and learning interests. towards understanding physical science (= 44,03 > 3.97), 3) Understanding of physical science groups of children with higher learning interest was taught by the discovery learning method than the project base learning method (= 17,53 > 3.96), 4) Physical science understanding of groups of children with low learning interest is taught by the discovery learning method than the project-based learning method (= -5.12 <3.96).